PENGARUH PROFITABILITAS, LIKUIDITAS DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN INDUSTRI FOOD AND BEVERAGE - Wanda Dwi Pebrianti; Fatimah Riswati (Fakultas Ekonomi dan Bisnis Universita Wijaya Putra Surabaya, 2024)
The study's goal is to analyse and contrast the profitability, liquidity, and dividend policies of different organisations. The population of this research consists of all firms that will have been in operation in the food and beverage industry in the years 2021–2023. The purposive sampling method was used to identify 17 different companies. The method of quantitative associative research is used in this investigation. The financial statements utilised in this research are secondary data obtained using a documentation-based method and were retrieved from the website of the Indonesia Stock Exchange. This method of data analysis makes use of descriptive statistics, tests of classical assumptions, multiple linear regression tests, and hypothesis testing. The data was statistically analysed using SPSS version 26. The results of the T test demonstrate that liquidity positively impacts firm value, dividend policy negatively impacts it, and partial profitability has no appreciable positive impact on firm value. Profitability, liquidity, and dividend policy do not interact strongly to affect the value of food and beverage companies listed on the IDX in 2021–2023.